Having the Father and the Son – the Structure, Main Theological Idea and Hermeneutical Principle of the Second Epistle of John - Wojciechowska, Kalina; Rosik, Mariusz (The Biblical Annals, 2023)
The Second Epistle of John is one of the least commented on New Testament writings, with the vast majority of existing commentaries being linear. The authors of this article attempted to take a structural view of this short book. After discussing the structures of the letter proposed by scholars (part one), they proposed their own structure of the book, thanks to which the main theological idea of the letter (2 John 9) (part two) could be determined, along with a hermeneutical principle allowing for new interpretative insights into the book as a whole (part three). This principle can be put into the words: “having the Father and the Son.”